Responses to financial stress at life transition points - Ryan, C (My University, 2012)
This paper looks at how changes in individuals’ circumstances affect their reported perceptions of their own financial wellbeing or deprivation. The aim is to assess how the experience of key life ‘transition’ points changes individuals’ reported financial positions. Examples of such key changes include: forming long-term relationships, starting a family, purchasing a house, leaving full-time education, and entering and leaving the workforce.
Keywords: Employment -- Exit from employment (Retirement/Redundancy); Life Events -- Impact; Employment; Education and Training; Families; Housing; Disadvantage, adversity and resilience; Ageing; Labour market; Education and Training; Families; Housing; Life Events; Employment; Impact; Exit from employment (Retirement/Redundancy); Dsiadvantage, adversity and resilience; Ageing; Employment and unemployment; Adversity and resilience